Faktor - Faktor Yang Mempengaruhi Prevalensi Ketidakcukupan Konsumsi Pangan di Indonesia - Mike Triani; Rahmiyatin Nisa (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This study aims to determine and analyze how the impact of the number of poor people, rice production, and food expenditure on the prevalence of undernourishment in Indonesia from 2018 - 2022. This study uses secondary data sourced from the Badan Pusat Statistik (BPS). With research variables grouped into two parts, namely the dependent variable which in this study uses the prevalence of undernourishment and the independent variable consisting of the number of poor people, rice production, and per capita food expenditure. This study uses panel data regression analysis using the Fixed Effect Model (FEM) method. The results showed that the variable number of poor people has a positive and significant effect on the prevalence of undernourishment, the variable rice production has a negative and significant effect on the prevalence of undernourishment and the variable per capita food expenditure has a positive and significant effect on the prevalence of undernourishment in Indonesia. This study provides a deeper understanding of the factors that influence the prevalence of undernourishment in Indonesia. The results of this study can also be used as a basis for formulating more effective policies related to public food consumption in Indonesia.